Sharia Internal Control towards Organizational Commitment: Implementation and its’ Implication - Abdul Azis (Universitas Muhammadiyah Malang, 2020)
This study aimed to investigate the correlation between organizational commitment, organizational culture, ownership structure, good corporate governance and internal sharia control. The participants of the study consisted of 244 active employees working as leaders at the Surgical Department of Andi Makkasau Hospital, Parepare. The Partial Least Square (PLS) path modelling was used in data analysi. Employees who have high organizational commitment and can implement internal sharia control in doing their work will have better performance. This can help reduce the rate of employee turnover and increasing employee attendance rates and also become intellectual property in the field of Islamic economics.